Anthropocene Accountability Litigation: Confronting Common Enemies to Promote a Just Transition - Abate, Randall (Columbia Journal of Environmental Law, 2021)
This article offers a new perspective in the quest for climate justice. Myriad accountability lawsuits in the U.S. have been filed against the fossil fuel and industrial animal agriculture industries in the past few years, but these efforts have proceeded without coordination between the environmental and animal law fields. There has been no scholarly inquiry that unites the efforts to seek relief from “common enemies” for exacerbating the climate change crisis while profiting from their operations. The article first reviews the climate change impacts from the fossil fuel and industrial animal agriculture industries and examines how federal regulatory gaps and subsidies enable and exacerbate the climate change impacts from these industries. It then reviews legal theories in common law accountability litigation against these industries that seek damages for the harms these industries cause to public health and welfare, the environment, and animals. The article proposes that accountability litigation against the fossil fuel and industrial animal agriculture industries can facilitate a transition away from reliance on fossil fuels and factory farms to more sustainable alternatives. Positive outcomes from several related contexts including tobacco litigation, the phaseout of harmful substances in environmental regulation, and the COVID-19 crisis support the urgent need for this “just transition.”